WELFARE EFFECTS OF ELETRICITY AND PETROL PRICE HIKE ON URBAN HOUSEHOLDS IN BENUE STATE - ONOV, Godwin Asemaver; Ayila , NGUTSAV; IJIRSHAR, Victor Ushahemba; NWOGU, Jorji Akudo (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2021)
This study examines the welfare effects of electricity and petrol price hike on urban households in Benue state. The Marshallian demand theory and the theory of utility were utilized. A three-stage sampling approach was used to obtain data from 384 urban households using a survey research design. For data analysis, the researchers employed Seemingly Unrelated Regression (SUR) and Compensating Variation (CV). The study found that both economic and social factors influence demand for electricity and petrol, and that increases in the prices of the energy goods (electricity and petrol) had negative impact on urban households' welfare in Benue State. The study recommends better supply distribution channel of electricity and petrol through public-private partnership and that government should ensure stable prices and supply of the two energy products over a long period of time.